Philosophy, literature and the problem of meaning - Katayama Omura, Roberto Juan (2014)
Here we will try to deal with the meaning of terms, more precisely the factors that influence, if they do not determine, the meaning of our words. To do this we will use texts classified as “philosophical” as well as “literary”.